MOTIFS AND SYMBOLS IN THOMAS HARDY’S THE MAYOR OF CASTERBRIDGE - Siti Rahmah (Multilingual, 2015)
The motifs means an element that is meaningful and that are repeated in one or a number of works. In asingle work, the motive is the meaning of the smallest elemenin the story, while a symbol is a person,object, or event that suggest more than its literal meaning. A literary symbol can include traditional,conventional, or public meaning, but it may also be estabilished internally by the totalcontext of the workin which it appears. A literary symbol can be setting, character, action, object, name, or anything else inwork that maintains its literal significancewhile suggesting other meanings.The problem studied in thisresearch is the study of the psychology literature on the motives and symbols of the existing characters inthe novel The Mayor of Casterbridge. The goal of this research is to discover, collect the fullest thendescribe disclosure motifs and symbols of the existing characters in the novel The Mayor of Casterbridgeis. The method used is the method of the study of literature (literature research), descriptive, and informalmethods. The result of the discussion showed that The Motif novel ofThe Mayor of Casterbridge areCoincidence, The Tension between Tradition and Innovation, and The Tension between Public Life andPrivate Life. The symbolof the existing main character in the novel The Mayor of Casterbridge are Redand Black, Bridge, Five Guineas, The Casterbridge Ring, The Caged Goldfinch, The Bull, and TheCollision of Wagen.